Account of the expenses of the Funeral of Mrs Barbara Ruthven, Daughter-in-Law of Sir Hugh Paterson of Bannockburn, 20th July 1695. From the original belonging to Hugh J Rollo (Proceedings of the Society of Antiquaries of Scotland, 1858)
This paper quotes an account of George Porteous' heraldry work associated with the funeral of Barbara Ruthven. Meeting notes for 12 May, 1856 are appended.